The global credit cycle - Nina Boyarchenko; Leonardo Elias (Federal Reserve Bank of New York, 2024)
Do global credit conditions affect local credit and business cycles? Using a large cross-section of equity and corporate bond market returns around the world, we construct a novel global credit factor and a global risk factor that jointly price the international equity and bond cross-section. We uncover a global credit cycle in risky asset returns, which is distinct from the global risk cycle. We document that the global credit cycle in asset returns translates into a global credit cycle in credit quantities, with a tightening in global credit conditions predicting extreme capital flow episodes and declines in the stock of country-level private debt. Furthermore, global credit conditions predict the mean and left tail of real GDP growth outcomes at the country level. Thus, the global pricing of corporate credit is a fundamental factor in driving local credit conditions and real outcomes.
Keywords: F30; F44; G15; G12; 330; global financial cycle; corporate bond returns; return predictability; international capital flows; credit and real activity outcomes